Follow-Ups on Persistent Symptoms and Pulmonary Function Among Post-Acute COVID-19 Patients: A Systematic Review and Meta-Analysis - Long, Qiuyue; Li, Jiwei; Hu, Xiaoyi; Bai, Yangyuyan; Zheng, Yali; Gao, Zhancheng (Frontiers in Medicine, 2021)
Objective: As the number of recovering COVID-19 patients increases worldwide, the persistence of symptoms and signs through the post-acute phase indicates an urgent need for prolonged follow-up care. To explore existing data about post-acute COVID-19 syndrome, this meta-analysis assesses the prevalence of persistent manifestations in multiple systems and abnormalities in lung function, as well as their related risks in patients with various severities. Methods: Articles about discharged COVID-19 patients (published from January 1, 2020 to February 23, 2021) were obtained by searching four databases. Cohort studies with follow-up periods > 1 month post-discharge or > 2 months post-admission were included. Results: A total of 4478 COVID-19 patients from 16 cohort studies were included in this meta-analysis. Fatigue or weakness (47%) were the most prevalent physical effects of post-acute COVID-19 syndrome, while psychosocial (28%) symptoms were the most common manifestations among several systems. Abnormalities in lung function of recovering patients, i.e., DLCO < 80% (47%, 95%CI: 32%-61%) persisted for long periods. Severe patients were more likely to present joint pain (OR 1.84, 95%CI: 1.11-3.04) and decreased lung functions compared with non-severe patients, with pooled ORs for abnormal TLC, FEV1, FVC, and DLCO of 3.05 (95%CI: 1.88-4.96), 2.72 (95%CI: 1.31-5.63), 2.52 (95%CI: 1.28-4.98), and 1.82 (95%CI: 1.32-2.50), respectively. Conclusions: Our research indicates that patients recovering from COVID-19 manifest long-term, multi-system symptoms, and the adverse effects on psychosocial health and lung functions were the most extensive and persistent. These findings together may facilitate much needed in-depth study of clinical treatments for long-term, post-acute phase symptoms that affect a great number of recovering COVID-19 patients.